Critical power is related to cycling time trial performance - Smith, J. C.; Dangelmaier, B. S.; Hill, D. W. (International Journal of Sports Medicine, 1999)
The purpose of this study was to evaluate critical power (W(CP)) as an indicator of aerobic fitness in trained cyclists, and to determine its relationship to cycling time trial (TT) performance. Thirteen competitive USCF category 2 or 3 cyclists provided season's best 40 km TT times (mean [SD]) time = 59.6 min (3.1), and performed two 17 km TT under controlled conditions (26.6 min [1.1]). Ventilatory threshold (VT) and VO2max were determined from a maximal incremental test. W(CP) was calculated using the results of four all-out constant power tests. Mean W(CP) was 299 (61) W or 4.1 W x kg(-1), VT was 3616 (750) ml x min(-1) or 49.8 ml x kg(-1) x min(-1) (7.5), and VO2max was 4596 ml x min(-1) or 63.5 ml x kg(-1) x min(-1) (8.0). W(CP) was strongly related to VT and VO2max, demonstrating that it can serve as a measure of aerobic fitness in this population. Expressions of W(CP) were slightly to considerably more highly related to 17 km and 40 km TT performances (r = -0.77 to -0.91) than were expressions of VT and VO2max (r = -0.71 to -0.87). It is concluded that W(CP) provides an aerobic fitness measure for competitive cyclists which can be obtained without invasive testing. In addition, W(CP) is strongly related to the TT performance of competitive cyclists.